Revision of the Genus Physiphora Fallén 1810 (Diptera: Ulidiidae: Ulidiinae) - Kameneva, Elena P.; Korneyev, Valery A. (Zootaxa, 2016)
The genus Physiphora includes at least 29 species, most of them occurring predominantly in the Afrotropical Region and a few species native to the other regions of the Old World. At least P. alceae (Preyssler 1791) and P. clausa (Macquart 1843) are subcosmopolitan species unintentionally introduced into the Australasian, Nearctic, and Neotropical Regions. Twelve new species from the Afrotropical Region are described: P. hendeli sp. n., P. igniceps sp. n., P. kirki sp. n., P. maraisi sp. n., P. meyi sp. n., P. opalizana sp. n., P. orinigra sp. n., P. polita sp. n., P. rugosa sp. n., P. spriggsi sp. n., P. steyskali sp. n., and P. virens sp. n. Detailed illustrated descriptions and a key for identification are provided for all the species of Physiphora. Analysis of the new and previously known biological data shows that larvae of most Physiphora species are saprophagous associated with rotting tissues of palms (apparently infested by the palm weevils), giant Euphorbia, and even baobabs and poplars. Some species are attracted to (and as larvae possibly can develop in) the dung of ungulates. The following synonymy is established: Physiphora clausa (Macquart 1843) = Physiphora hainanensis Chen in Chen & Kameneva 2007: 24, syn. n.; Physiphora flavipes (Karsch 1888) = Chrysomyza africana Hendel 1909, syn. n., = Cliochloria senegalensis Enderlein 1927, syn. n.